Dictyostelids from Mediterranean forests of the south of Europe - Romeralo, María; Lado, Carlos (Mycological Progress, 2006)
The first results of a study of dictyostelid diversity in soils of Mediterranean vegetation are presented. Surface soil samples were collected during 2003–2004 from different Mediterranean forests in Spain and Portugal and were plated out for cellular slime moulds. Isolated during this study were 14 species of dictyostelids. One species, Dictyostelium firmibasis is reported for the first time from Europe, and nine (Dictyostelium aureo-stipes, Dictyostelium sp. 1, Dictyostelium fasciculatum, Dictyostelium giganteum, Dictyostelium implicatum, Dictyostelium leptosomum, Dictyostelium sphaerocephalum, Polysphondylium candidum, Polysphondylium pallidum) are new records for the Mediterranean region. Members of the three genera Dictyostelium (ten species), Polysphondylium (three species) and Acytostelium (one species) are present in this region of the world. Comments on their diversity and distribution are included.
Keywords: Dictyostelids; distribution (PG); diversity; mediterranean forest soils